Assistance in Management of BUMDes Sumberdem Gemilang in Realizing Village Economic Independence - Robbi Readi; Rofiqi; Agung Winarno; Aini, Desti Nur (Jurnal Pengabdian Masyarakat, 2025)
Purpose: Village-Owned Enterprises (BUMDes) play a vital role in community welfare but often face challenges due to limited resources and managerial capacity. This program aims to develop BUMDes based on local assets in Sumberedem Village, Malang Regency. Method: The program applies the Asset-Based Community Development (ABCD) approach, focusing on asset identification and strengthening managerial skills. Practical Application: Program results show improved BUMDes managerial capabilities in business planning, financial management, and marketing. Asset identification also spurred new community-driven economic initiatives, supporting business diversification and increasing BUMDes income. Conclusion: The assistance significantly boosted the village economy, reinforcing BUMDes’ role in promoting welfare. Continued support and stronger partnerships with private and government sectors are needed to sustain progress.